Bail-In and Interconnectedness: Strategic Legal Issues in Preventing and Handling Financial System Crises - M. Faisal Rahendra Lubis; Syalwa Khairun Nisa; Dwi Purnama Sari; Anggi Saskia Jelita Daulay; Fanny Aurellia Hasyim Lbn Tobing; Ahmad Ryandi Nst (International Journal of Economic, Technology and Social Sciences (Injects), 2026)
Law No. 9 /2016 on the Prevention and Resolution of Financial System Crises regulated principles in the prevention and handling of financial system crises that were not previously regulated. Therefore, this study will analyze the implementation of bail in principle and, interconnectedness in the prevention and resolution of financial system crises. This research was conducted using normative juridical method with analytical descriptive approach and data was analyzed by juridical qualitative. Based on the research, the results show that the implementation of bail-in in handling of systemic banks is done by optimizing bank capability through capital surcharge. The interconnectedness between the financial services sector requires a macro prudential policy complementary to micro prudential policy, and integrated supervision of the financial services sector.